The impact of government subsidies on microplastic pollution control in mariculture: an evolutionary game theory analysis in Qingdao, China - Haiming Song; Xinting Wang; Xiaomeng Huan; Lin Yang (Frontiers in Marine Science)
Mariculture constitutes the primary origin of microplastic pollution, necessitating immediate action to address microplastic pollution by focusing on both the supply and demand aspects of fishing gear. Based on the cooperative management model of mariculture microplastic pollution, this paper develops an evolutionary game model that incorporates the interactions among fishing gear enterprises, fishermen, and the government. It then proceeds to examine the government’s strategy for managing mariculture microplastic pollution through game theory and simulation analysis. The main findings obtained are as follows. (1) The management of mariculture microplastic pollution can be improved on both the supply chain and market aspects by implementing subsidies. The likelihood of receiving government subsidies boosts the production of environmentally-friendly fishing gear by fishing gear enterprises and the purchase of such gear by fishermen. (2) Based on the cost-benefit variations for fishing gear enterprises, fishermen, and the government, the evolutionary game model reaches distinct equilibrium states, leading to corresponding adjustments in the optimal government subsidy strategy. (3) While there are some positive effects of subsidies, increasing government subsidies does not necessarily lead to better outcomes. As the total amount of subsidies increases, the best practice for governments would be to phase out subsidies for environmentally-friendly fishing gear. Accordingly, the government should build a multi-subject collaborative governance model, reasonably control subsidies amount, prevent the adverse consequences of excessive subsidies, and optimize the structure of subsidy recipients.